Morpheus: Dreamscape architectural operations - Adika Ramaghazy; Yandi Andri Yatmo (Department of Architecture Faculty of Engineering Universitas Indonesia, 2023)
This study explores the narrative of dreams as a basis of architectural design operation. This study positions its exploration within a dreamscape; or a surrealist situation that becomes the basis of architectural design. Current architectural discourse has explored design based on some structured and rigid operations. However, understanding dreamscape as a design medium positions the importance of explorative and unstructured operations as the basis of the alternative spatial narrative. Morpheus is a title of experimental architecture programming in this design study which is driven by a series of speculative dream operations. This study employs dream narratives to develop architectural programming languages, from the initial exploration to the materialisation of its architecture. In this study, architecture emerge as an experimental instrument based on speculative and unstructured operations of dreamscape, as an alternative method in constructing narrative relationships.